Re-Transmission Assessment Survey Filariasis Pasca Pengobatan Massal di Kabupaten Agam, Provinsi Sumatera Barat Tahun 2016 - Santoso Santoso; Sri Cahyaningrum (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Agam District finished the repetition of Filariasis treatment for 2 years, so Agam must be conducting the Re-TAS. Re-TAS was conducted on elementary school students grade 1 and 2 in the district of Agam. Survey design using the school cluster. The number of schools selected were 40 schools. Selection of the sample schools were calculated using sample survey builder (SSB). All students grades 1 and 2 in selected schools were examined using Brugia Rapid test to assess the presence of specific antibodies against Brugia malayi and B. timori worms. The number of students who registered as many as 1,999 children, while being examined by RDT as many as 1,717. A total of 282 students were absent during the examination or refused to be examined.Test results showed that 3 positive, 1694 negative, 20 invalid and 3 samples were excluded. The number of samples taken into account to assess the transmission of filariasis as many as 1,697, which is only positive and negative samples. The survey found that the minimum sample was adequate and the number of positive children under the cut off point, so Agam passed TAS 1.